(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Creativity - the activity of a person and its result that determines the significance and usefulness of a particular innovation. A creative person is a person who can successfully carry out a creative process and has specific creative results (products). A creative person is a person who demonstrates creativity as a process or result, is inclined to approach solving problems in non-standard ways, is capable and ready to organize original actions, promote innovations, create creative products. A creative person is a person who implements objective creativity both as a process and as a result and is able to create creative products at the required level.